Ferroptosis-Related Hub Genes in Hepatocellular Carcinoma: Prognostic Signature, Immune-Related, and Drug Resistance Analysis - Wang, Wei; Pan, Fan; Lin, Xinrong; Yuan, Jiakai; Tao, Chunyu; Wang, Rui (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC) is the most prevalent type of primary liver cancer with high fatality rate and dismal prognosis because of frequent recurrence and lack of efficient therapies. Ferroptosis is a recently recognized iron-dependent cell death distinguished from necroptosis and apoptosis. The relationship between ferroptosis-related Hub genes expression and prognosis in HCC remains to be further elucidated. Methods: We obtained ferroptosis-related genes from the FerrDb database and the mRNA sequencing data and clinical information of HCC patients from The Cancer Genome Atlas (TCGA) database. The least absolute shrinkage and selection operator (LASSO) Cox regression was applied to identify a prognostic signature consisting of 5 ferroptosis-related Hub genes in the TCGA cohort. International Cancer Genome Consortium (ICGC) database was utilized to validate the reliability of the signature. Functional enrichment and Immune-related analysis including single-sample gene set enrichment analysis (ssGSEA), immune checkpoints and m6A related genes were performed to analyze the underlying mechanism. Additionally, the correlations of ferroptosis and drug resistance were evaluated by the NCI-60 database. Results: A 5-ferroptosis-related Hub genes signature was constructed by multivariate Cox regression analysis to stratify patients into two risk groups. Patients with high-risk had worse prognosis than those with low-risk. Multivariate Cox regression analysis uncovered that the risk score was an independent prognostic indicator. We also proved the signature's predictive capacity using Kaplan–Meier method and Receiver operating characteristic (ROC) curve analysis. Functional analysis showed that nuclear division and the cell cycle were enriched. Immune-related analysis revealed that the signature was enriched in immune-related pathways. Moreover, we found substantial difference in immune cells infiltration, immune checkpoints and m6A-related genes between high-risk and low-risk groups. Furthermore, these genes were crucial regulators of drug resistance. Conclusion: We identified and validated a novel ferroptosis-related Hub genes signature as a new and efficient biomarker with preferable potential for predicting the prognosis of HCC patients. What’s more, it also offers new insights into the molecular mechanisms of HCC and provides an effective approach for the treatment of HCC. Further studies are necessary to validate these results of our study.